Protestant Missionaries Are Associated With Reduced Community Cohesion - Hager, Anselm (Sociology of religion, 2022)
Do Protestant missionaries affect community cohesion? This study puts forth two mechanisms that link missionaries to trusting, cooperative community life: pro-social preferences and social networks. On the one hand, Protestant missionaries espouse charity, and they establish regular venues of social interaction. On the other hand, Protestant missionaries propagate an individualist faith, and they provide an identity along which communities may separate. The effect of Protestant missionaries on community cohesion is thus unclear. To make headway on these conflicting theoretical predictions, we study variation in missionary activity in southeastern Peru. We document that villages with Protestant missions show lower levels of community cohesion compared to non-missionized, Catholic villages. We point to weakened networks as the most likely causal channel and show that effect sizes are particularly large among Pentecostal missionaries.